Strategies to increase red color and reduce the incidence of sunburns on apples - Gabardo, Gentil Carneiro; Santos, Keli Cristina dos; Fenili, Cristhian Leonardo; Petri, José Luiz; Schveitzer, Bianca; Parizotto, Bruno Scapinelli (Scientia Agraria Paranaensis, 2020)
The aim of this study was to evaluate the application of CaCO3 in liquid formulation on the incidence of sunburn and the visual quality of apples, as well as to test application times and dosages of biostimulants in increasing the red Color of the fruits. The study was carried out in partnership with the rural producer, in the orchards located in the municipality of Fraiburgo-SC, in the 2018/2019 harvest. To meet the proposed objectives, two different experiments were conducted: experiment 1 - application of calcium carbonate to reduce the incidence of sunburn in apples and experiment 2 - use of biostimulant to increase the red Color in the epidermis of apples. The variables analyzed were: production data (kg plant-1, fruits plant-1, average fruit mass and aspects related to fruit quality: pulp firmness, soluble solids content, mineral content in fruits, percentage of red Color in the epidermis of the fruits and incidence of sunburn. The tests carried out to promote the red Color of the fruits showed satisfactory results. However, the tests developed aiming at reducing the incidence of sunburn did not show reliable results, since the environmental conditions, mainly the sunstroke, were not favorable to the development of the damage to the fruits, making it impossible to obtain conclusive information on the efficiency of the CaCO3 product. in reducing the incidence of sunburn in apples. The application of CaCO3 as a sunscreen does not improve the calcium content of the harvested fruits. The application of Physiogrow® Color promotes better allocation of the harvested fruits in categories of greater coloration of the epidermis.